Spatial structure in European moose (Alces alces): genetic data reveal a complex population history. (27th June 2014) - Niedziałkowska, Magdalena; Hundertmark, Kris J.; Jędrzejewska, Bogumiła; Niedziałkowski, Krzysztof; Sidorovich, Vadim E.; Górny, Marcin; Veeroja, Rauno; Solberg, Erling J.; Laaksonen, Sauli; Sand, Håkan; Solovyev, Vyacheslav A.; Shkvyria, Maryna; et al.
Abstract Aim Moose, Alces alces (Linnaeus, 1758), survived the European Pleistocene glaciations in multiple southern refugia, in a northern refugium near the Carpathians and possibly in other locations. During the second millennium ad, moose were nearly extirpated in Europe and only recolonized their current range after World War II. The number and location of refugia during the Pleistocene and recent population lows may have affected the current genetic diversity. We sought to characterize the genetic diversity in European moose in order to determine its genetic structure and the location of genetic hotspots as a way of inferring its population history and the number of Last Glacial Maximum (LGM) refugia. Location Europe. Methods We sequenced 538 nucleotides from the mitochondrial control region of 657 moose from throughout the species' European range. We estimated diversity within and among 16 sampling localities, and used samova to cluster sampling locations into subpopulations. We constructed phylogenetic trees and median‐joining networks to examine systematic relationships, and conducted Bayesian analysis of the coalescent and used mismatch distributions and approximate Bayesian computation to infer demographic history. Results Estonia had the highest nucleotide diversity, and western Belarus had the highest haplotype diversity. We observed four regional populations from the samova analysis. We found three haplogroups in European moose, probably representing lineages conserved in different refugia during the Pleistocene. European moose underwent spatial expansion after the LGM, but did not undergo demographic expansion. The effective population size has declined markedly within the last 2000 years. Main conclusions The current levels and distribution of genetic diversity in European moose indicate the effects both of Pleistocene glaciations and of a recent bottleneck, probably associated with anthropogenic influences such as pastoralization and hunting, and a very recent re‐expansion. We show that both historical and recent events can influence the diversity and distribution of a large mammal on a large scale.